THE CONCEPTUAL OUTLINE OF PERCEPTION IN TERMS OF GREIMASSIAN SEMIOTIC THEORY - Anna Zaslonkina (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2018)
The current study addresses the nature of the relation between perceptual, cognitive, emotional processes, and linguistic experience within the observer framework. As an extension of the already conducted investigations into the semiotics of the sensible, the conceptual triad SENSE : FEELING : EMOTION is introduced. The study argues that the ternion in question is a component of human expressivity constituting the semiotic space of the thymic category. The synergism of cognitive-semantic characteristics of the three concepts under study corresponds to the basic level of categorisation in modern English. More significantly, the aim of the analysis is to consider the valency models of the names of the conceptual triad SENSE : FEELING : EMOTION as well as their collocability potential. The present paper highlights that the structures of predicate valency of conceptual dependencies FEELING → SENSE (the valency index equals 0,38) outnumber the analogous structures FEELING → EMOTION (the valency index equals 0,24). The structures of object valency of the combinations FEELING → EMOTION (the valency index is 0,9) prevail over the combinations SENSE → FEELING (with the valency index of 0,1). The data obtained confirm the idea that the correlation between observer and observable is twofold: cognitive-perceptual correlation denotes the observer's outward perspective, whereas cognitive-emotional correlation denotes the observer's inward perspective.